Surface Crystallization in Mg-Based Bulk Metallic Glass during Copper Mold Casting - Xin Wang (Advances in Materials Science and Engineering)
The localized crystallization of Mg54Cu28Ag7Y11 bulk metallic glass (BMG) in the injection casting process using a copper mold was investigated. It has been found that several crystalline phases were formed close to the as-cast surface but did not exist in the internal part of the BMG plate. It is abnormal that the as-cast surface is partially crystallized with higher cooling rate than that of inside. Overheating of the melt and nucleation induced by the surface of copper mold play key roles in the abnormal crystallization. It is suggested that the function of copper mold to trigger heterogeneous nucleation cannot be totally ignored, although it provides the high cooling rate for the glass formation during casting.